Delivery of essential pediatric congenital surgical care within Brazil's universal health coverage system: a national survey of pediatric surgeons - Luke Caddell; David P Mooney; Fabio Botelho; Kathrin Zimmerman; Nivaldo Alonso; Alexis Bowder; Bellisa Caldas Lopes; Simone Abib; Paul R Truche; Abbie E Naus; Julia Ferreira; Isabella Maria de Freitas Faria; et al. (BMJ Publishing Group, 2023)
Objective In this study, we assess the delivery of congenital pediatric surgical care under Brazil's system of universal health coverage and evaluate differences in delivery between public and private sectors.Methods A cross-sectional national survey of pediatric surgeons in Brazil was conducted. Participants were asked which of 23 interventions identified through the Disease Control Priorities 3 (Surgical Interventions for Congenital Anomalies) they perform and to report barriers faced while providing surgical care. Responses were weighted by state and stratified by sector (public vs private).Results A sample of 352 responses was obtained and weighted to represent 1378 practicing pediatric surgeons registered in Brazil during the survey time. 73% spend the majority of their time working in the public sector ('Sistema Único de Saúde' and Foundation hospitals), and most of them also work in the private sector. Generally, Brazilian pediatric surgeons have the expertise to provide thoracic, abdominal, and urologic procedures. Surgeons working mostly in the public sector were more likely to report a lack of access to essential medications (25% vs 9%, p<0.01) and a lack of access to hospital beds for surgical patients (52% vs 32%, p<0.01).Conclusions Brazilian pediatric surgeons routinely perform thoracic, abdominal, and urologic surgery. Those working in government-financed hospitals face barriers related to infrastructure, which may impact Brazilians who rely on Brazil's universal health coverage system. Policies that support pediatric surgeons working in the public sector may promote the workforce available to provide congenital pediatric surgical care.